Simultaneous Assessment of Left Ventricular Volumes and Aortic Valve Annular Dimensions by Three-Dimensional Speckle-Tracking Echocardiography in Healthy Adults from the MAGYAR-Healthy Study—Is There a Relationship? - Nemes Attila (LIFE-BASEL, 2025)
Introduction: Three-dimensional speckle-tracking echocardiography (3DSTE) can be used to accurately measure the dimensions of the left ventricle (LV) and aortic valve anulus (AVA) at the same time. The present study aimed to conduct an extensive 3DSTE-based investigation of simultaneously assessed end-diastolic and end-systolic LV volumes and AVA dimensions in healthy adults with LVs and AVAs of different sizes. Methods: One hundred and seven healthy adults (mean age 35.4 ± 12.2 years, 67 males) were voluntarily enrolled in the present study. Results: With increasing end-diastolic AVA area, tendentious increase in both end-diastolic and end-systolic LV volumes could be detected, resulting in preserved LV-EF. With increasing end-systolic AVA area, similar findings were present. Comparing the smaller than mean and the larger than mean end-systolic AVA area subgroups, the end-systolic LV volume proved to be significantly increased in the latter group. With the increase in end-diastolic LV volume, the AVA dimensions remained preserved. With the increase in end-systolic LV volume, only the highest end-systolic LV volume was associated with larger end-systolic AVA area and perimeter; the other parameters remained preserved. In certain circumstances, end-systolic AVA area and perimeter proved to be significantly increased compared to their end-diastolic counterpart. Conclusions: With the increase in end-diastolic and end-systolic AVA areas, a tendentious increase in both LV volumes could be detected in healthy adults. Larger end-diastolic LV volume was not associated with dilated AVA dimensions, while larger end-systolic LV volume was associated with dilated end-systolic AVA area and perimeter.